A model to predict early hepatic encephalopathy in patients undergoing transjugular intrahepatic portosystemic shunt - Li, Yinglong; He, Xiaofeng; Pang, Huajin (Turkish Journal of Gastroenterology, 2019)
Background/Aims: Early hepatic encephalopathy (HE) is one of the most common complications developed after undergoing transjugular intrahepatic portosystemic shunt (TIPS). Hence, its early prevention and treatment are important. This study aimed at establishing a model to predict early post-TIPS HE.Materials and Methods: Clinical data of 262 patients who underwent TIPS procedure was analyzed retrospectively. Patients were divided into early post-TIPS HE and non-early post-TIPS HE groups, based on the presence of HE within 3 months after TIPS. About 70% of the patients were randomly selected as the model group to establish a prediction model, and the remaining 30% were used as the validation group to test the model. The independent risk factors for early HE post-TIPS were identified and selected using single factor analysis and multi-factor logistic regression analysis. Subsequently the prediction model was established and validated.Results: Age, Child-Pugh classification, and fibrinogen were found to be the independent risk factors for early post-TIPS HE., The logistic regression model was established based on these factors and their regression coefficients: p=1/{1+exp[4.829−1.975*age−1.110*(Child-Pugh classification)+1.724*loge (fibrinogen in g/L)]}. Finally, the model was validated among a set of 79 patients from the validation group.Conclusion: The logistic regression model based on age, Child-Pugh classification, and fibrinogen for early post-TIPS HE can effectively predict the risk of early HE after TIPS.